Perbandingan Penyelesaian Sengketa Arbitrase Online Antara Indonesia Dengan Cina : Sebuah Tinjauan Hukum - Bintang, Cantika Ramadhani; Sumanto, Listyowati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Dispute resolution through online arbitration has become an increasingly important topic in the context of international business relations. This article provides a comprehensive legal review of the comparison of online arbitration dispute resolution between Indonesia and China. Through in-depth analysis of the legal system, contract provisions, technology used, economic considerations, and the influence of government regulations, the author explains the differences and similarities that exist between the two countries in resolving this dispute. The different legal approaches between Indonesia, which adopts a legal system based on civil law, and China, which has a legal system based on Confucian law and socialist law, are the main focus of discussion. As a result, this article identifies the key factors that influence the effectiveness of online arbitration dispute resolution between Indonesia and China and provides valuable insights for legal practitioners, entrepreneurs and researchers interested in this field. In conclusion, this article emphasizes the importance of a deep understanding of the differences in legal and regulatory culture between the two countries in designing successful dispute resolution strategies in the context of online arbitration.